Late results of arthroscopic and open anterior acromioplasty - (:unkn) unknown (My University, 2004)
OBJECTIVES: We evaluated the results of arthroscopic or open anterior acromioplasty after a mean follow-up of two years in the treatment of impingement syndrome. METHODS: The study included 145 patients who underwent anterior acromioplasty through open surgery (90 patients; mean age 56 years; range 36 to 70 years) or arthroscopic surgery (55 patients; mean age 49 years; range 32 to 58 years). Comparisons were made between both groups with regard to preoperative and postoperative Constant scores, activity, pain, range of motion, and strength scores, and durations for postoperative pain, hospital stay, and return to work. The mean follow-up was 24 months (range 12 to 60 months) for both groups. RESULTS: The mean Constant scores increased from preoperative 32.6 to postoperative 80.5 and from 25.5 to 83.1 with open and arthroscopic surgery, respectively. No significant differences were found between the two groups with regard to pre- and postoperative Constant scores, activity, pain, range of motion, and strength scores (p>0.05). However, patients who underwent arthroscopic surgery exhibited shorter durations in the following: hospital stay (1.36 vs 1.72 days), delay in return to work (9 vs 16 days), and postoperative pain (6 vs 8 weeks) (p<0.05). According to subjective patient evaluations, arthroscopic results were good or excellent in 47 patients (85.5%), satisfactory in six patients (10.9%), and poor in two patients (4.6%); open surgery results were good or excellent in 76 patients (84.4%), satisfactory in 10 patients (11%), and poor in four patients (4.6%). CONCLUSION: Both treatment options seem to be equally effective in the treatment of impingement syndrome in the absence of rotator cuff tears.
Keywords: Adult; Female; Humans; Middle Aged; Postoperative Complications; Treatment Outcome; Male; Pain, Postoperative; Radiography; Range of Motion, Articular; Length of Stay; Shoulder Impingement Syndrome; Arthroscopy; Acromioclavicular Joint; Acromion; Arthroplasty